Pengaruh Beban Kerja Dan Budaya Organisasi Terhadap Turnover Intention Dengan Komitmen Organisasional Sebagai Variabel Mediasi Pada Karyawan CV Surya Buana - Ni Putu Ayu Sintya Saraswati; Ni Made Satya Utami; Ni Made Kusuma Wardani (CV. ITTC INDONESIA, 2025)
This study aims to determine the role of organizational commitment in mediating the influence of workload and organizational culture on turnover intention at CV Surya Buana, Denpasar. The research objects include 41 employees of CV Surya Buana, with the sample selected using a saturated sampling technique. The Partial Least Square (PLS) model was employed for data analysis. The results show that workload has a positive and significant effect on turnover intention, while organizational culture has a negative and significant effect. Organizational commitment has a positive and significant effect on turnover intention. Workload negatively and significantly affects organizational commitment, whereas organizational culture positively and significantly influences organizational commitment. Indirectly, workload increases turnover intention through organizational commitment, while organizational culture reduces turnover intention via organizational commitment. This study highlights the importance of managing workload and strengthening organizational culture to reduce turnover intention by enhancing organizational commitment.